Mixtec evangelicals: globalization, migration, and religious change in a Oaxacan indigenous group - O'Connor, Mary I., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
Mixtec Evangelicals is a comparative ethnography of four Mixtec communities in Oaxaca, detailing the process by which economic migration and religious conversion combine to change the social and cultural makeup of predominantly folk-Catholic communities. The book describes the effects on the home communities of the Mixtecs who travel to northern Mexico and the United States in search of wage labor and return having converted from their rural Catholic roots to Evangelical Protestant religions. O'Connor identifies globalization as the root cause of this process. She demonstrates the ways that neoliberal policies have forced Mixtecs to migrate and how migration provides the contexts for conversion. Converts challenge the set of customs governing their Mixtec villages by refusing to participate in the Catholic ceremonies and social gatherings that are at the center of traditional village life. The home communities have responded in a number of ways--ranging from expulsion of converts to partial acceptance and adjustments within the village--depending on the circumstances of conversion and number of converts returning. Presenting data and case studies resulting from O'Connor's ethnographic field research in Oaxaca and various migrant settlements in Mexico and the United States, Mixtec Evangelicals explores this phenomenon of globalization and observes how ancient communities are changed by their own emissaries to the outside world. Students and scholars of anthropology, Latin American studies, and religion will find much in this book to inform their understanding of globalization, modernity, indigeneity, and religious change.--Provided by publisher.
Chapter 1. Ñuu Shaavi, The Land of Rain. A Brief History of the Mixteca Region -- The Spanish Conquest and Afterward -- Political Organization in the Mixteca Area -- Politics in Mixtec Villages: Usos y Costumbres -- Politics and Religion -- Migration and Religious Change -- The Churches -- The Conversion Process -- Hermana Adela-Migrant and Convert -- Non-Catholic Churches in the Mixteca Region -- The Response of the Catholic Church to Religious Change -- Conclusion -- Chapter 2. Mixtecs and Modernity. Modernity, Indigeneity, and Religious Conversion -- Modernity and Religion -- "The Great Transformation" -- Globalization and Neoliberalism -- Mixtecs in the New World Order -- Globalization, Migration, and Modernity -- Cultural Remittances -- Mixtec Communities in the Context of Globalization -- Globalization and Religious Conversion -- Indigenous Modernities -- Conclusion -- Chapter 3. San Juan Mixtepec: Ñuu Vicu, the Land of Clouds. The Municipio -- The Setting -- Two Agencias: San Lucas and San Pedro Yososcuá -- Discussion -- Relations between Catholics and Non-Catholics -- Non-Catholic Churches in Yososcuá Discussion -- Relations between Catholics and Non-Catholics in Yososcuá -- Migration and Religious Change -- Social and Economic Indicators -- Modernity and Usos y Costumbres -- Chapter 4. San Juan Diquiyú: Village on a Rock. Why San Juan Diquiyú? -- The Setting -- The Village of San Juan Diquiyú -- The Fiesta System -- Orthodox and Folk Catholicism -- Non-Catholics in San Juan Diquiyú -- Seventh-Day Adventists -- Trinitarians in San Juan Diquiyú -- Conflict, Peace, and Ridicule -- Discussion -- Chapter 5. Colonia Sinaí: Los Expulsados. Introduction -- The Village -- The Expulsion -- After the Expulsion -- The Return to the Village -- Discussion -- Chapter 6. Four Communities Compared. Variations on a Theme -- The Settings -- Language and Religion -- Socioeconomic Characteristics of the Communities -- Migration and Community Development -- Catholics and Non-Catholics -- Usos y Costumbres in Three Communities -- Migration, Religious Change, and Modernity -- Chapter 7. Mixtec Diaspora? Introduction -- Mixtec Migrants in Mexico -- Conversion in Culiacán -- Miguel Alemán, Sonora -- Non-Catholics in Miguel Alemán -- Baja California -- San Quintín -- Tijuana -- Mixtecs in the United States -- California -- Oregon and Washington -- Discussion -- Generations, Present and Future -- Ethnic Organizations -- The IJA: An Alternative to Ethnic Organizations? -- Mixtec Diaspora? -- Chapter 8. Concluding Remarks. Mixtecs in the Modern World-System -- Transnational Communities and Religious Conversion -- Mixtec Villages as Transnational Communities -- Transnational Studies, Globalization, and Religious Conversion -- Selective Modernity -- Toward a General Explanation of Religious Conversion.
Keywords: Mixtec Indians -- Mexico -- Oaxaca (State) -- Religion; Mixtec Indians -- Migrations; Return migrants -- Mexico -- Oaxaca (State); Return migration -- Mexico -- Oaxaca (State); Evangelicalism -- Mexico -- Oaxaca (State)